2014
DOI: 10.1007/s11999-014-3793-5
|View full text |Cite
|
Sign up to set email alerts
|

Minorities Are Less Likely to Receive Autologous Blood Transfusion for Major Elective Orthopaedic Surgery

Abstract: Background Surgeons commonly arrange for patients to perform autologous blood donation before elective orthopaedic surgery. Understanding sociodemographic patterns of use of autologous blood transfusion can help improve quality of care and cost containment. Questions/purposes We sought to determine whether there were (1) racial disparities, (2) insurance-based disparities, or (3) income-based disparities in autologous blood use. Additionally, we evaluated the combined effect of (4) race and insurance and (5) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Factors including limited access to care, low health literacy, and a higher prevalence of risky behaviors (e.g. drug and alcohol abuse) may be at the heart of the poorer prognosis associated with underinsured patients and those living in rural areas [32][33][34][35]. It is also possible that these patients were referred to less experienced and less specialized surgeons, or that they were more likely to utilize the ED instead of going to the physician's office for an infection [33,36].…”
Section: Discussionmentioning
confidence: 99%
“…Factors including limited access to care, low health literacy, and a higher prevalence of risky behaviors (e.g. drug and alcohol abuse) may be at the heart of the poorer prognosis associated with underinsured patients and those living in rural areas [32][33][34][35]. It is also possible that these patients were referred to less experienced and less specialized surgeons, or that they were more likely to utilize the ED instead of going to the physician's office for an infection [33,36].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have assessed the role of race and ethnicity on the incidence of intraoperative complications. Menendez and Ring 16 analyzed the perioperative risks of different racial groups following any major elective orthopedic procedure, as identified by the NIS, the largest allpayer inpatient database in the country containing discharge records from over 1,000 hospitals (n=3.5 million patients). They found that Hispanics were less likely than Caucasians to receive a blood transfusion during a THA (OR, 0.75; 95% CI, 0.69 to 0.82; P<.001) or a TKA (OR, 0.71; 95% CI, 0.67 to 0.75).…”
Section: Intraoperative Complicationsmentioning
confidence: 99%
“…1 Multiple studies have shown that racial minorities undergo TJA much less frequently than Caucasians. [8][9][10][11][12][13][14][15] Furthermore, studies have shown higher complication rates among these ethnic minorities, [16][17][18][19][20][21][22][23][24] and some have even showed an association between disparities and patient-reported and functional outcomes. [25][26][27][28] The following review will highlight more specific details of these disparities and outcome differences.…”
mentioning
confidence: 99%
“…Concerning AT, patient's blood can be collected using different strategies among which the most frequently applied are the following ones: 1) preoperative autologous collection/donation (PAD); 2) acute normovolemic hemodilution (ANH); and 3) perioperative blood recovery/salvage (PBR). In addition, the scheme of PBR includes: a) intraoperative blood collection/salvage (IBC) from the surgical field, and b) postoperative blood collection/drainage (PBC) by aspiration 1,[14][15][16][17][18][19][20][21][22] . Independently or combined, these AT-strategies proved to reduce the needs for allogeneic blood in elective surgery.…”
Section: Regardless Of the Implementation Of Different Effective Prevmentioning
confidence: 99%
“…Opinions regarding efficiency of PBC in orthopedic surgery are not unanimous and the following should be taken into consideration: 1) prospect studies to illustrate the benefits of transfusion of "saved" blood; b) make analyses of risks of transfusion of unprocessed blood, taking into special consideration possible contamination of blood with bacteria or chemical agents (e.g. metylmetakrylat) and 3) analysis of cost vs benefit aspects 6,[14][15][16][17][18][19][20][21][22] .…”
Section: Perioperative Blood Recovery/salvagementioning
confidence: 99%